The prevalence of urinary incontinence and its impact on quality of life among the university female staff in South Africa - L. Skaal; M.K. Mashola (AOSIS, 2011)
Background: Urinary incontinence (UI) is a common problem among females and has been associated with significant decreased quality of  life. Few  women  seek  help  for  this  condition  with  only  a  few  who consult physiotherapy treatment.Purpose: To determine the prevalence of urinary incontinence and its impact on quality of life among the university women in South Africa.Method:  A  quantitative  cross-sectional  study design  with  145  women  ran-domly selected from the university. A questionnaire was used to determine UI Diagnosis; Impact on Qol and treatment seeking tendencies. BMI was meas-ured objectively. ethical clearance was obtained from University. Data was analysed using SPSS 17.0Results:  Forty  six(32%)  women  reported  to  having  UI.  Risk  factors  associated  with  UI  included  age,  race,  and  obesity. UI had a significant negative impact on quality of life and only 4.4% of participants with UI consulted physio-therapy for this condition.Conclusion: There is a high prevalence of UI among the women at this university with a significant impact on quality of life.The role of Physiotherapy in management of UI has been demonstrated and there is therefore a need to empower women with non-invasive treatment options, like physiotherapy.